Formação de classes funcionais de estímulos musicais - Machado, Alex Roberto (2008)
A behavioral approach of music considers the musical action as behavior and the music as stimuli, this action s product. The general objective here proposed was to verify the discriminative training s effect above mode and tempo different melodies functional classes formation. Participants: 9 of Unilinhares students (Linhares ES) second period psychology s graduation, divided in three groups. Each group was submitted in one of the experimental conditions (mode, tempo or mix). For data collect was utilized a software, especially designed for this study - SomPsi which executed all the participants training and generated reports with informations about their performance, fase by fase. Fase 1: baseline, presented 6 sound stimuli twice; Fase 2, relation AB trained; Fase 3, the BC relation (in this two fases were presented 4 stimuli, 5 times each); Fase 4: functional classes formation test, organized similarly to Fase 1. Data showed that this research s objectives were reached, because the training was efficient to musical stimuli s functional classes formation. There were differences between participants performance in the experimental conditions, corroborating with researches findings, as found in theme s revision, just like: stimuli grouping by tempo property were easier to discriminate than those grouped by the mode. Thus, combined manipulation of the two properties, in convergent condition, allowed even better participants performance, like showed in "Mix" condition.